Analysis of subsurface structure in ulakan tapakis district Padang Pariaman regency using refraction seismic method - Syafriani, Syafriani; Adzura, Nadilla (Universitas Ahmad Dahlan, 2024)
Analysis of Subsurface Structure in Ulakan Tapakis District, Padang Pariaman Regency Using Refraction Seismic Method. This study aims to analyse the subsurface structure in Ulakan Tapakis District, Padang Pariaman Regency using the seismic refraction method. Data acquisition used the in-line configuration technique on eight passes. The data obtained form of wave traveltime as a function of distance. Data processing the refraction seismic method is based on the arrival time of the first wave, by picking the first break to obtain a travel time graph and using time-term inversion to obtain a 2-D seismic cross section. The results showed that the subsurface structure in the study area consisted of 2 layers based on differences in wave propagation velocity on each path. Wave velocities in the first layer of 252 m/s to 425 m/s are interpreted as layers of weathered bedrock, topsoil, unsaturated sand and gravel mix at depths of 1 to 6 meters. The second layer has wave velocities of 503 m/s to 665 m/s interpreted as layers of alluvium, saturated sand and gravel at depths greater than 6 meters. The subsurface structure in this area is included in the primary structure with rock formation units in the form of surface Alluvium (Qal) deposits which are suspected of experiencing subsurface weathering. This research makes a significant contribution to mitigating the risk of earthquake disasters by providing an understanding of the potential associated hazards.